Attributions of the pharmacist in the rational use of medicines and self-medication (Research, Society and Development, 2021)
The present study aimed to assess the responsibility of the pharmacist regarding the rational use of medications. The rational use of medications became a concern when the problems caused by the abuse of these substances became frequent for health professionals, it is observed that the ease of purchasing medications has contributed to the spread of irrational use, along with these factors as well. there is a tendency towards self-medication, a tendency that is very present in our society and makes irrational use in evidence when dealing with medications. Today we have a wide variety of medicines with unlimited access, which made it possible to purchase medicines on a large scale, causing risks arising from inappropriate use, which was supposed to cause a good to become a major problem for the consumer's health. The study results were organized in a table, attributing the year of publication, authors, title and characteristics of the work that reinforced the need for attention to the rational use of medicines. Aiming that the consumption of medicines becomes more and more frequent and that the pharmaceutical market grows every day, the importance of ensuring the safety in the use of these medicines was highlighted and the concern of health professionals with regard to patient safety was intensified. expressly related to the direct participation of the pharmacist in this promotion of rational use.